Health-Information Seeking and Intention to Quit Smoking: Do Health Beliefs Have a Mediating Role?. (August 2019) - Upadhyay, Soumya; Lord, Justin; Gakh, Maxim
Background: Smoking is a leading cause of preventable deaths. Smoking cessation can reduce the risk of smoking-associated disease and death. But smoking cessation involves behaviour change. Existing research indicates that health-information seeking and health-promoting behaviours can be positively associated. However, in the context of smoking, the relationship between seeking health information and intending to quit smoking remains only partially understood. Aim: This study aimed to examine the relationship between seeking health information and intending to quit smoking and to determine whether this relationship is mediated by health beliefs. Methods: We used data from the fourth cycle of the US National Cancer Institute's Health Information National Trends Survey (HINTS). Logistic regression was used to assess the independent variable (ie, health-information seeking) and dependent variable (ie, intention to quit smoking) as mediated by health belief. Results: Our findings suggest that smokers who seek health information have a 2.67 times higher odds of intending to quit smoking than smokers who do not seek health information. However, health beliefs do not have an intervening effect between seeking health information and intending to quit smoking. Discussion: Seeking health information is important in predicting attempts to quit smoking, regardless of the smokers' pre-existing health beliefs. Our findings support cessation efforts that encourage smokers to seek health information. Determining optimal ways to encourage smokers to seek smoking-related information could support achieving and maintaining smoking cessation. Conclusion: Cessation programmes and policies should encourage smokers to seek health information. Additional research should further examine smokers' motivators and cues for health-information seeking and should further probe smokers' beliefs about the risks of smoking.